Effect of feed on the performance of upgraded Holstein Friesian bulls during fattening at BAPARD cattle farm in Bangladesh - Mustafa, MMH; Islam, MR; Rahman, MM (Asian Journal of Medical and Biological Research, 2021)
The study was conducted to find out the effect of beef cattle diet on the performance of upgraded Holstein Friesian bulls at BAPARD cattle farm in Bangladesh. For this purpose, twelve Local x Holstein-Friesian upgraded bulls (L×F) of average 20 months of age and 213 kg live weight were divided into three equal groups. Three different diets such as (i) a mixed concentrate ration (T1), (ii) mixed concentrate ration and UMS at a ratio of 1:1 on DM basis (T2) and (iii) green Grass based ration without concentrate and UMS. The results found that the average daily live weight gains of three groups was 350g, 330g and 340g respectively, which were not differ significantly (P<0.05). Daily DM intake was significantly higher in T3 but the digestibility found lower than other treatments. In case of feed conversion ratio (FCR), the highest FCR was found in T1 (2.96) but cost of per kg live weight gain was the lowest in T3 (BDT 90) compared to T1 (BDT 140) and T2 (BDT 142). Therefore, considering the FCR and cost of per unit beef production, a beef diet of green grass might be the appropriate diet for the floodplains area for Local x Holstein-Friesian upgraded bulls. Asian J. Med. Biol. Res. December 2020, 6(4): 761-767